Equably-dispersed Sb/Sb2O3 nanoparticles in ionic liquid-derived nitrogen-enriched carbon for highly reversible lithium/sodium storage. (1st November 2021) - Wang, Zhaomin; Zeng, Fanming; Zhang, Dongyu; Wang, Xinyu; Yang, Weiling; Cheng, Yong; Li, Chun; Wang, Limin
Abstract: Antimony anode has attracted increasing attention with its suitable voltage platform and high theoretical capacity. Nonetheless, its actual application is largely hindered by the capacity loss due to the volume effect during the cyclic process. Herein, A novel polyhedral structure nitrogen and carbon doped Sb/Sb2 O3 (Sb/Sb2 O3 -NC) nanoparticles are designed via a liquid phase reaction approach followed by a thermal treatment process. The nanocomposite anode used for lithium-ion batteries (LIBs) delivers a reversible specific capacity as high as 460 mAh g −1 after 100 cycles at 2 A g −1 and excellent rate performance of 353 mAh g −1 at 10 A g −1 . In addition, at a current density of 500 mA g −1, Sb/Sb2 O3 -NC exhibits a capacity of 318 mAh g −1 after 100 cycles and excellent rate performance of 183 mAh g −1 at 2 A g −1 for sodium-ion batteries (SIBs). The results suggest that the polyhedral Sb/Sb2 O3 -NC could be a potential candidate as anode material for LIBs and SIBs.